Ezh2 inhibition in Kras-driven lung cancer amplifies inflammation and associated vulnerabilities - Serresi, Michela; Siteur, Bjorn; Hulsman, Danielle; Company, Carlos; Schmitt, Matthias J; Lieftink, Cor; Morris, Ben; Cesaroni, Matteo; Proost, Natalie; Beijersbergen, Roderick L; van Lohuizen, Maarten; Gargiulo, Gaetano (The Journal of experimental medicine, 2018)
Kras-driven non-small-cell lung cancers (NSCLCs) are a leading cause of death with limited therapeutic options. Many NSCLCs exhibit high levels of Ezh2, the enzymatic subunit of polycomb repressive complex 2 (PRC2). We tested Ezh2 inhibitors as single agents or before chemotherapy in mice with orthotopic Kras-driven NSCLC grafts, which homogeneously express Ezh2. These tumors display sensitivity to EZH2 inhibition by GSK126 but also amplify an inflammatory program involving signaling through NF-κB and genes residing in PRC2-regulated chromatin. During this process, tumor cells overcome GSK126 antiproliferative effects. We identified oncogenes that may mediate progression through an in vivo RNAi screen aimed at targets of PRC2/NF-κB. An in vitro compound screening linked GSK126-driven inflammation and therapeutic vulnerability in human cells to regulation of RNA synthesis and proteostasis. Interestingly, GSK126-treated NSCLCs in vivo also showed an enhanced response to a combination of nimesulide and bortezomib. Thus, Ezh2 inhibition may restrict cell proliferation and promote defined adaptive responses. Targeting these responses potentially improves outcomes in Kras-driven NSCLCs.